A Critical Review of Canva as a Visual Media Platform for English Learning - Khakim, Agi Khafidh Al; Wahidah, Farah Sukmawati; Wirabhakti, Agus (Green Publisher Indonesia, 2024)
This article reviews the use of online visual media platforms for English language learning, revealing that these platforms influence learners' motivation, participation, skill assessment, and collaborative learning environments. The review also highlights the need for further research on the integration of visual media in English language acquisition, particularly in reputable publications like Scopus and Google Scholar. This study also focuses on the writer's existing knowledge and aims to develop their own application of analysis based on their learning from related works. A total of 17 articles were retrieved from two online databases: the SCOPUS database and the Google Scholar website, using keywords related to the theme of online Visual media platforms accommodating online learning experiences and the effectiveness of onlinevisual media platforms. The study incorporated three research approaches: qualitative, quantitative, and mixed-method Research design methodology. The findings indicated the need of using all three research methods to get a legitimate and robust result for data interpretation in the field of education when using Canva as an online visual medium platform.